Public K-12 Education Response to Serving Special Education Students During COVID: A Content Analysis - Burleigh, Cheryl L.; Wilson, Andrea M.; Bean, Erik (Journal of the American Academy of Special Education Professionals, 2023)
From the onset of COVID-19, public K-12 schools were scrambling to keep classrooms open virtually providing all students with meaningful learning experiences. This study provides a synthesis of insights gained about K-12 special education service provision during COVID. A content analysis benchmarking approaches to serving special education K-12 students during COVID-19 included a review of current literature, government, state documentation, and public advocacy data revealed the complexities of this issue. When services are not provided, the school is out of compliance, directly affecting students’ educations and the funding the school district receives to support special education programs. Furthermore, when school districts lacked the forethought to anticipate the unexpected or address how to serve students remotely, students were left to fend for themselves. This disruption in legally mandated services detrimentally affected these students and their special education teachers, paraprofessionals, parents, as well as caregivers.